Self-destructive behavior in patients with psychotic disorders of the schizophrenia spectrum - Pyliagina Галина; Bashinskiy Олександр (Psychosomatic Medicine and General Practice, 2020)
The present study assesses the difference in motivation of SDB and SI was found in different groups. In Gr1 PermSDB the main motivation was psychological problems associated with mental illness, social and interpersonal problems, while in Gr2 ImpSI the exclusive reason of SI was «command» to do it under influence of imperative pseudo-hallucinations. They were 95 patients with schizophrenia, schizoaffective disorder and acute polymorphic psychotic disorder examined in this issue and divided into 2 groups according to the pathways types of SDB: the first group – patients with permanent features of SDB as comorbid disturbance (Gr1 PermSDB), the second group – patients with impulsive SDB manifestations as secondary behavior disturbance on background acute psychotic episode with imperative pseudo-hallucinations (Gr2 ImpSI). There was a weighty predominance of patients with schizophrenia and hallucinatory-paranoid syndrome in both groups. Patients with schizophrenia more frequently realized impulsive SI exactly with imperative pseudo-hallucinations as the cause of them. Results confirmed that fundamentally diverse pathways for SDB manifestation and dynamic of it, also SI motivation exist in patients with SSPsD. It should be taken in the treatment tactic and rehabilitation course for such different patients.